NO-ERGIC SCARS SYSTEM AND IS NOT DAMAGED SKIN - Stavitskіy, S.A.; Neporada, K.S.; Avetikov, D.S.; Sukhomlin, A.A. (World of Medicine and Biology, 2012)
We determined the influence of NOS activity and concentrations of nitrite-anions on the type of scar tissue. We observed 92 patients, 43 and 49 in each study group. NO-synthase activity was determined by the difference in the concentrations of nitrite. The concentration of nitrite anions was determined by the formation of diazo compounds in the reaction with sulfanilic acid. Patients of the first group (keloid scars), the activity of NO-synthase and nitrite anion content significantly increased. That UTB promotes collagen activity.
Keywords: hypertrophic scars; keloids; NO-synthase; nitrite anions; fibroblasts